2018
DOI: 10.1016/j.compositesb.2018.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on fatigue performance of adhesively bonded anchorage system for CFRP tendons

Abstract: This study is concerned with the fatigue performance of adhesively bonded anchorage for carbon fiber reinforced polymer (CFRP) tendons subjected to cyclic loading. Series of monotonous and cyclic experiments under different stress amplitudes and loading frequencies were carried out in order to investigate the mechanical performance of bonded anchorage systems for CFRP tendons and to study the influence of cyclic loading on the anchoring performance. The fatigue damage and the relationships between damage, load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Based on these results, the overall anchorage performance is clarified and anchorage mechanism is also clearly expounded. [112][113][114][115][116][117][118] Wedge-type anchorage system…”
Section: Bond-type Anchorage Systemmentioning
confidence: 99%
“…Based on these results, the overall anchorage performance is clarified and anchorage mechanism is also clearly expounded. [112][113][114][115][116][117][118] Wedge-type anchorage system…”
Section: Bond-type Anchorage Systemmentioning
confidence: 99%
“…Experimental studies on the fatigue properties of CFRP rods have revealed that the anchoring system used for the fatigue test of a CFRP rod must be well-designed to prevent slippage and severe premature fiber failure within the anchoring section. Xie et al [23] investigated slippage and the variation of bonding interfacial temperature in a bonded anchorage system during the fatigue-loading process, revealing their impact on the ultimate anchoring capacity. Song et al [24] proposed a novel wedge-type anchorage system that could withstand fatigue stress amplitudes from 200 MPa to 800 MPa and maximal stresses from 0.37 to 1.0 fu without slippage or failure in the anchoring section.…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt et al [ 11 ] investigated the bonded and non-bonded FRP tendon system, showing that there are concerns on how to achieve reliable anchorage due to brittleness of the tendons, low strength perpendicular to the fiber direction and insufficient stress transfer in anchorage/tendon interface. The performance of present anchorage has been investigated to improve the layout, and some novel anchorage cable system has also been proposed [ 12 , 13 , 14 , 15 , 16 , 17 ]. Winistoerfer et al [ 18 , 19 ] studied the pin-loaded looped CFRP strap and suggested it can be used as practical tensile elements since the load can transfer through the pins without the requirement of additional anchoring systems.…”
Section: Introductionmentioning
confidence: 99%